PENGAMALAN M-PEMBELAJARAN DALAM KALANGAN GURU NOVIS PENDIDIKAN ISLAM DI SABAH: THE PRACTICES OF M-LEARNING AMONG ISLAMIC EDUCATION NOVICE TEACHERS IN SABAH - Miasan, Nur Atikah; Tengku Kasim, Tengku Sarina Aini (Journal of Islamic Educational Research, 2018)
This descriptive review research was conducted to determine the level of practices for the implementation of mobile learning towards Islamic Education Novice Teachers (ISNT) who served in Sabah, by using qualitative methods. This reseach had interviewed four informants from four different zone in Sabah. The findings showed that they have basic preparations in terms of obtaining mobile devices and having basic skills in handling it for learning and facilitating students. In addition, they used various applications from online and offline to support their teaching and learning session by using mobile devices. All of these findings are not affected by gender or teaching areas factor (such as urban, rural or remote areas).